Perceived stress and academic procrastination among higher vocational nursing students: the mediating roles of positive and negative emotions - Congjie Cao; Dandan Chen; Yi Zhou (BMC Nursing)
Abstract Background Academic procrastination is particularly prevalent among higher vocational nursing students, a key component of the nursing workforce, and is closely associated with poor academic performance and a decline in clinical practice quality. While perceived stress and emotions are known significant predictors, the mechanisms through which they influence academic procrastination remain unclear. Thus, this study aimed to explore the mediating roles of positive and negative emotions in the relationship between perceived stress and academic procrastination among higher vocational nursing students. Methods A cross-sectional survey was conducted among 1308 higher vocational nursing students from June to July 2023 in Hebei Province, China. The participants were recruited by convenient sampling to complete a sociodemographic and academic related information questionnaire, Perceived Stress Scales, Positive and Negative Affect Schedule, and Academic Procrastination Questionnaire for College Students. Then, the data were analysed by SPSS 26.0 and a multiple mediation model was tested using Hayes’ PROCESS macro (Model 4). A mediation effect was considered statistically significant if the 95% confidence interval did not contain zero. Results The mean score of academic procrastination was 50.4 (12.6), with 82.0% of nursing students reporting academic procrastination. A significant positive correlation was observed between perceived stress, negative emotions and academic procrastination (r = 0.442, r = 0.376, all P < 0.001). Conversely, a significant positive correlation was found between positive emotions and academic procrastination (r=-0.299, P < 0.001). Subsequent mediation analysis demonstrated that positive emotions and negative emotions partially mediated the correlation of perceived stress with academic procrastination (total indirect effect: Standardized β = 0.193, 95% CI [0.142, 0.247]). The direct effect was 0.252, and the mediating effect accounts for 43.4% of the total effect. Conclusions Positive and negative emotions act as partial mediators in the correlation between perceived stress and academic procrastination among higher vocational college nursing students. It is crucial for nurse educators to foster positive emotional experiences and alleviate negative emotions through strategies such as effective stress management and mindfulness practices, in order to mitigate academic procrastination. Limitations As a cross-sectional study, it cannot establish causal relationships between perceived stress, positive and negative emotions, and academic procrastination. Clinical trial number Not applicable.